2014
DOI: 10.1177/0960327114527629
|View full text |Cite
|
Sign up to set email alerts
|

Fasting ameliorates metabolism, immunity, and oxidative stress in carbon tetrachloride-intoxicated rats

Abstract: Background: Fasting has been recently discovered to improve overall health, but its beneficial effects in the presence of hepatic insufficiency have not been proven. Aim: The influence of fasting on the metabolism, immunological aspects, and oxidative stress of 40 male carbon tetrachloride (CCl4)-intoxicated Wistar rats was investigated in the present study. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…In support of our results, it was previously found that CCl 4 augmented lipid peroxidation in liver of rats. 18 As previously noticed by Naaz et al, 21 the increase in LPO concentration might be returned to the hindrance of enzymatic antioxidants (e.g. GSH-P X activity) and the consumption of non-enzymatic antioxidants (e.g.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In support of our results, it was previously found that CCl 4 augmented lipid peroxidation in liver of rats. 18 As previously noticed by Naaz et al, 21 the increase in LPO concentration might be returned to the hindrance of enzymatic antioxidants (e.g. GSH-P X activity) and the consumption of non-enzymatic antioxidants (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…SOD, CAT, and GSH-P X are the important antioxidant enzymes responsible for removing free radicals in cells. Sadek and Saleh 18 reported that the administration of CCl 4 significantly decreased the total antioxidant capacity and antioxidant enzyme activities in the serum of fasted rats. We recently reported that α-LA enhanced the antioxidant capability of GSH-P X enzymes and elevated the GSH content in the livers of broiler chickens fed aflatoxicosis diets and diabetic rats, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty male carbon tetrachloride-intoxicated Wistar rats were exposed to RIF mimicking model, and the results showed significant reductions in CRP and MDA parameters for OS. [ 49 ] In a similar RIF mimicking model, Shawky et al . showed that IF caused a considerable increase in neutrophil phagocytic activity, phagocytic index, and brain neurotransmitters (norepinephrine and serotonin).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used to identify serum principal metabolites and investigate the mechanism of exogenous material on organisms ( 21 24 ). In animal hepatotoxicity studies, toxic chemicals such as carbon tetrachloride ( 25 ), organophosphorus pesticide ( 26 ), and NDEA ( 27 ) significantly disrupted the level of several metabolites in blood, including arachidonic acid, lysophosphatidyl ethanolamines, and phosphatidylcholine. A metabolomic study of hepatotoxicity induced by chlorpyrifos and cadmium found that chlorpyrifos and cadmium could disrupt the energy, amino acid, and fatty acid metabolism in rat liver ( 28 ).…”
mentioning
confidence: 99%